Individual determinants associated with utilisation of sexual and reproductive health care services for HIV and AIDS prevention by male adolescents - Omari Shabani; Mary M. Moleki; Gloria G.B. Thupayagale-Tshweneagae (AOSIS, 2018)
Background: Adolescent sexual and reproductive health is one of the essential health care programmes in the world. However, adolescents still face numerous challenges in the area of sexual and reproductive health, which hinder their utilisation of available Sexual and Reproductive HealthCare Services (SRHCS). Male adolescents face further obstacles in accessing and utilising sexual reproductive health services owing to the influence of social constructions of masculinity, which has a bearing on how they view sexual and reproductive health services and their use. Objectives: The aim of this study was to investigate individual determinants associated with utilisation of SRHCS for HIV and AIDS prevention by male adolescents. Method: An exploratory, descriptive and contextual qualitative design was used and semi-structured interviews with 20 purposively selected male adolescents aged 18-24 years living in the South African seat of government were conducted. Data were analysed using Tesch's approach of data analysis. Results: Knowledge of existing services was described as a significant individual determinant of utilisation of SRHCS. This was linked to the quality of SRHCS and violation of human rights of male adolescents. Conclusion: The study recommends the development of a strategy that will enhance and promote the utilisation of SRHCS by male adolescents.